Associations of Job Insecurity With Perceived Work-Related Symptoms, Job Satisfaction, and Turnover Intentions: The Mediating Role of Leader–Member Exchange and the Moderating Role of Organizational Support - Di Stefano, Giovanni; Venza, Gaetano; Aiello, Davide (Frontiers in Psychology, 2020)
This study wants to examine effects of job insecurity on several work-related outcomes (perceived work-related symptoms, job satisfaction, and turnover intentions) by developing a moderated mediation model. The model emphasizes the role played by the quality of leader-member exchange (LMX) in mediating the relation between perceived job insecurity and outcomes related to work, and the moderating role of perceived organizational support (POS) in influencing the mediation. Survey data from 510 workers at Italian organizations were collected and regression were used to evaluate the hypotheses. After age, gender, education and organizational tenure were controlled, results showed that perceived quality of LMX carried the effect of job insecurity on all outcomes, and that this relationship was stronger for employees who reported higher levels of POS. This study makes important theoretical and practical contributions to job insecurity, LMX and POS research, underlining the importance of promoting the leader-member relationship’s quality in an ethic and supportive work environment.